Competitive manufacturing - Mather, Hal (Prentice Hall, 1988)
Considered one of the top manufacturing experts in the U.S., Mather has helped hundreds of companies worldwide to achieve astonishing bottom-line results through total manufacturing excellence. In this classic guide he spells out specific ways manufacturers of all sizes can use new methods and technologies to cut inventories, lead times, and costs while realizing gains in quality and service.